2011
DOI: 10.1093/glycob/cwr014
|View full text |Cite
|
Sign up to set email alerts
|

NMR and molecular modeling reveal key structural features of synthetic nodulation factors

Abstract: Nod factors are lipochitoligosaccharides originally produced by the soil bacteria Rhizobia that are involved in the symbiotic process with leguminous plants. Some synthetic analogs of the Nod factors present a strong biological activity, and the conformational behavior of these molecules is of interest for structure/function studies. Nod factor analogs containing an insertion of a phenyl group in the acyl chain at the oligosaccharidic non-reducing end were previously synthesized (Grenouillat N, Vauzeilles B, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Several lines of evidence suggest that LysM modules belong to type B CBMs. Unlike crystalline cellulose, which forms a relatively flat surface recognized by type A CBMs, chitin oligosaccharides and peptidoglycan strands display a helical structure5051. Accordingly, the recent three-dimensional structure of A. thaliana CERK1 bound to a chitopentaose revealed that the sugar backbone binds in a shallow groove formed by the loops between strand 1-helix 1 and helix 2-strand 2 of the protein25.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that LysM modules belong to type B CBMs. Unlike crystalline cellulose, which forms a relatively flat surface recognized by type A CBMs, chitin oligosaccharides and peptidoglycan strands display a helical structure5051. Accordingly, the recent three-dimensional structure of A. thaliana CERK1 bound to a chitopentaose revealed that the sugar backbone binds in a shallow groove formed by the loops between strand 1-helix 1 and helix 2-strand 2 of the protein25.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are no available 3D structures of Rhizobium nodulation factors, which are characterized by a backbone of between three and five substituted (sulfonated) GlcNAc residues. Recent work has begun to address this knowledge gap with NMR and nanosecond-simulations (Morando et al 2011). Definition of nodulation factor SARs and generation of synthetic derivatives will accelerate production of non-leguminous plants that can fix nitrogen themselves, toward which our extended microsecond-simulations now contribute.…”
Section: Discussionmentioning
confidence: 99%
“…These geometric criteria have been used in previous studies of aqueous-phase systems. 63,64 The average bond lengths and their corresponding standard deviations of the important states along each studied reaction pathway are determined from all of the configurations falling into the region where the free energy is within ∼1.5 kcal mol −1 of each minimum.…”
Section: Energy and Fuelsmentioning
confidence: 99%